Push-Out Bond Strength of Experimental Apatite Calcium Phosphate Based Coated Gutta-Percha - Al-Haddad, Afaf Y.; Kutty, Muralithran Govindan; Che Ab Aziz, Zeti Adura (Hindawi Publishing Corporation, 2018)
Objectives. To evaluate the push-out bond strength of experimental apatite calcium phosphate coated gutta-percha (HAGP) compared to different commercially available coated gutta-percha root obturation points. Methods. Extracted teeth were selected and instrumented using ProTaper rotary files. The canals were assigned into five equal groups and obturated using matching single cone technique as follows: EndoREZ cones and EndoREZ sealer, Bioceramic Endosequence gutta-percha (BCGP) with Endosequence BC sealer, Active GP with Endosequence BC sealer (ActiV GP), conventional GP with Endosequence BC sealer, and HAGP with Endosequence BC sealer. Each root was sectioned transversally at the thickness of 1±0.1 mm to obtain 5 sections (n=25 per group). The specimens were subjected to push-out test using a Universal Test Machine at a loading speed of 0.5 mm/ min. Failure modes after push-out test was examined under stereomicroscope and the push-out data were analyzed using ANOVA and the post hoc Dunnett T3 test (p = 0.05). Results. The highest mean bond strength was yielded by HAGP followed by BCGP, ActiV GP, conventional GP, and EndoREZ. There were significant differences between EndoREZ and all other groups (p<0.001). The prominent failure mode of HAGP was mixed mode, whereas EndoREZ exhibited adhesive failure mode. Conventional GP, ActiV GP, and BCGP showed cohesive failure mode. Conclusion. HAGP showed promising results to be used as root canal filling material in combination with bioceramic sealer.